Epidemiología del cáncer colorrectal, según género y grupo etáreo, atendidos en el Hospital Solca Loja, durante el periodo 2006-2015, y su proyección al año 2020. - Juárez Macas, Carlos Fabricio (2017)
The demographic, epidemiological and nutritional transition experienced by developing countries determines changes and impacts on the life expectancy of the population, and establishes the pattern of historical behavior of diseases. When we observed the epidemiological parameters of incidence and mortality of chronic-degenerative pathologies, such as cancer, in countries geared towards economic growth, we evidenced a growing trend in the incidence and mortality of colorectal cancer. The objective of this study is to know the epidemiological reality of colorectal neoplasm in the province of Loja, establishing problems that can be studied, providing information that facilitates the development of health policies that may improve the quality of life of the population in the future. The research was developed with a quantitative, descriptive and retrospective design, having as population the patients diagnosed with colorectal cancer, and those who died during the period 2006-2015. Specific rates and standardized rates were calculated and represented in tables and graphs. The results show that the incidence of colorectal cancer has decreased in the 10 years of study, and the affection predominates in the masculine gender. Mortality reveals a predominantly female-dominated growth. Likewise, from the point of view of the age group, it is determined that patients over 65 years of age are more affected in both incidence and mortality. The existence of a variable epidemiological situation is determined in relation to that established in the global, regional or national dynamics. Key words: colorectal cancer, epidemiology, incidence, mortality, specific rate, standardized rate.